The Business Bookshelf. The Next Day: Transitions, Change, and Moving. - Hall, Amy (Key Words)
This article reviews *The Next Day: Transitions, Change, and Moving Forward* by Melinda French Gates, focusing on the book’s exploration of personal change through the author’s reflections on her life experiences. French Gates, known for her role in the Bill & Melinda Gates Foundation, shares insights from her upbringing, career at Microsoft, motherhood, and coping with loss, emphasizing meditation and introspection as tools for navigating transitions. The book is not a chronological memoir but a collection of thoughtful essays aimed at readers facing significant life changes. The review notes the absence of an index, which could have aided readers given the book’s non-linear structure and inclusion of various referenced individuals and poetry.